DFT/TD-DFT calculations on the sensing mechanism of a dual response near-infrared fluorescent chemosensor for superoxide anion and hydrogen polysulfides: photoinduced electron transfer. Issue 106 (2nd November 2016) - Sun, Xiao-Fei; Zhang, Zhi-Xiang; Li, Wei; Bai, Fu-Quan; Wang, Jian; Jia, Ran; Kong, Chui-Peng; Zhang, Hong-Xing
Abstract : Fluorescence quenching by the PET process in HCy-FN. Abstract : Previous studies have shown that intracellular O2 ˙ − /H2 Sn are related to cytoprotection processes. In order to detect these two important species spontaneously, a sensitive chemosensor HCy-FN has been developed. In the present study, the sensing mechanisms of the fluorescent chemosensor HCy-FN, its oxidation product Cy-FN and the elimination product Keto-Cy have been investigated in detail using density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methods. The present theoretical study indicates that there are intramolecular charge transfer (ICT) states in HCy-FN and Cy-FN, and they are energetically beneath the bright state, which is responsible for the photoinduced electron transfer (PET) process resulting in the fluorescence quenching. Whereas, Keto-Cy emits strong fluorescence because of the absence of PET. The calculated vertical excitation energies agree well with the experimental values and the calculation results can deeply explain the observed experimental phenomena.